2019
DOI: 10.1111/vde.12818
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a chloroquine‐induced canine model of pruritus and skin inflammation

Abstract: Background Chloroquine (CQ) is a prototypical systemic and intradermal pruritogen for histamine‐independent (nonhistaminergic) itch in mice and humans. The predictive validity of this model is poorly documented in dogs. Hypothesis/Objective To determine pruritogenic and inflammatory effects of systemic and i.d. CQ injections in healthy dogs. Animals Ten healthy purpose‐bred laboratory beagles. Methods and materials All dogs were randomized to receive i.d. (200 and 400 µg/site), intravenous (2 mg/kg) and subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 19 publications
(74 reference statements)
0
35
0
Order By: Relevance
“…Based on their active gene expression levels and significant upregulation compared to their expression at baseline, we identified IL‐33, IL‐13, CCL17, and IL‐9, and potentially IL‐6 and CCL22, as possible targets for inhibition which might complement the action of LKV. To support this, the upregulation of mRNA or protein expression of IL‐33, IL‐13, and CCL17 has been reported in the skin or sera of client‐owned dogs with AD compared to healthy dogs in multiple studies 27–31 . Some of these cytokines and chemokines (e.g., IL‐33, CCL17, IL‐6, CCL22) are produced at a very early stage of AD acute flare induction, which is likely to be even before Th2 cells produce IL‐31 32 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Based on their active gene expression levels and significant upregulation compared to their expression at baseline, we identified IL‐33, IL‐13, CCL17, and IL‐9, and potentially IL‐6 and CCL22, as possible targets for inhibition which might complement the action of LKV. To support this, the upregulation of mRNA or protein expression of IL‐33, IL‐13, and CCL17 has been reported in the skin or sera of client‐owned dogs with AD compared to healthy dogs in multiple studies 27–31 . Some of these cytokines and chemokines (e.g., IL‐33, CCL17, IL‐6, CCL22) are produced at a very early stage of AD acute flare induction, which is likely to be even before Th2 cells produce IL‐31 32 .…”
Section: Discussionmentioning
confidence: 95%
“…To support this, the upregulation of mRNA or protein expression of IL-33, IL-13, and CCL17 has been reported in the skin or sera of client-owned dogs with AD compared to healthy dogs in multiple studies. [27][28][29][30][31] Some of these cytokines and chemokines (e.g., IL-33, CCL17, IL-6, CCL22) are produced at a very early stage of AD acute flare induction, which is likely to be even before Th2 cells produce IL-31. 32 Therefore, the expression of mRNA was not likely to have been affected by IL-31 inhibition.…”
Section: Gene Codesmentioning
confidence: 99%
“…Interestingly, the results of these studies revealed multipolar immunological axis upregulation (Th1, Th2, Th17 and Th22) in cAD as is found in humans with AD. [10][11][12][13][14] This indicates that cytokine network activation in AD is, in fact, no longer considered to simply involve a specific group of cytokines (i.e. upregulation of only Th2 cytokines) and is instead the interplay between a large number of cytokines.…”
Section: Updates On Cytokines and Chemokines In Canine Atopic Dermatitismentioning
confidence: 99%
“…Concerning pruritus, CQ can bind to and activate the masrelated G protein-coupled receptors MrgprA3/MrgprX, which can be coupled to PLC-b3 or TRPA1 and so initiate pruritus [117]. The activation of this receptor is the main known mechanism of CQ-induced pruritus and even constitutes an animal model of itch [118]. More, opiate receptor, serotonin receptor, N-methyl-D-aspartate receptors, and gastrin-releasing peptide receptor are probably involved in this iatrogen itch, but exact mechanisms are unknown [119].…”
Section: Mechanismsmentioning
confidence: 99%